«Domostroy» by Xenophon and the model of an effective manager - V. M. Fedorov (Омский научный вестник: Серия "Общество. История. Современность")
The relevance and value of Xenophon’s «Domostroy» lies in the fact that it has an applied orientation and acts as a theoretical basis for the development of modern management. Xenophon’s «Domostroy» laid the foundations of the theory of management, it was the first to formulate an ideal model of the manager. Individual places of «Domostroy» are still able to arouse the interest of the manager-manager. The main objectives of the study are to identify the prerequisites for the use of the basic elements of the effective manager model, outlined in Xenophon’s «Domostroy», in order to develop the content of modern management theory. The theoretical and methodological basis of the study is the provisions and categorical apparatus of modern management concepts. In this article, general scientific theoretical research methods are used: historical-genetic and mentallogical methods (methods of abstraction, idealization and synthesis). The results of the work have important theoretical and methodological significance for the formation of professional consciousness of management based on centuriesold management practice.